2019
DOI: 10.1523/eneuro.0198-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Off-Target Effects in Transgenic Mice: Characterization of Dopamine Transporter (DAT)-Cre Transgenic Mouse Lines Exposes Multiple Non-Dopaminergic Neuronal Clusters Available for Selective Targeting within Limbic Neurocircuitry

Abstract: Transgenic mouse lines are instrumental in our attempt to understand brain function. Promoters driving transgenic expression of the gene encoding Cre recombinase are crucial to ensure selectivity in Cre-mediated targeting of floxed alleles using the Cre-Lox system. For the study of dopamine (DA) neurons, promoter sequences driving expression of the Dopamine transporter (Dat) gene are often implemented and several DAT-Cre transgenic mouse lines have been found to faithfully direct Cre activity to DA neurons. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 73 publications
6
33
0
Order By: Relevance
“…Such GABAergic responses and modulation of polysynaptic inhibition were observed also in TH-Cre mice ( Supplementary Fig. 6), although it should be noted that these different mice lines vary in the expression patterns of neurotransmitters in a topographic manner 75,76 .…”
Section: Discussionmentioning
confidence: 64%
“…Such GABAergic responses and modulation of polysynaptic inhibition were observed also in TH-Cre mice ( Supplementary Fig. 6), although it should be noted that these different mice lines vary in the expression patterns of neurotransmitters in a topographic manner 75,76 .…”
Section: Discussionmentioning
confidence: 64%
“…Several dopaminergic neuron-specific Cre recombinase expressing mouse lines (DAT-Cre) have also been created (Backman et al, 2006;Ekstrand et al, 2007;Turiault et al, 2007;Zhuang, Masson, Gingrich, Rayport, & Hen, 2005). Despite concerns about specificity of Cre expression (Papathanou, Dumas, Pettersson, Olson, & Wallen-Mackenzie, 2019) and spontaneous tamoxifen-independent recombination ("leakiness") of CreERT2 (Kristianto, Johnson, Zastrow, Radcliff, & Blank, 2017;Sandlesh, Juang, Safina, Higgins, & Gurova, 2018), these mouse lines have been extremely useful to study functions of multiple genes in dopaminergic neurons. For example, analysis of sonic hedgehog (Shh)/DAT-Cre mice revealed that Shh expression in dopaminergic neurons is essential for their maintenance in the adult animals, as the mutant mice exhibited neurodegeneration, locomotor, and gait abnormalities (Gonzalez-Reyes et al, 2012).…”
Section: Etiological Modelsmentioning
confidence: 99%
“…In addition to these key fate-determining transcription factors, fundamental for the midbrain DA neurons development, we also analyzed the expression of the Dopamine active transporter (DAT), which is responsible for dopamine reuptake from the synaptic cleft into the cytosol. DAT gene expression, the gold standard for the identification of mature dopaminergic neurons [16], was undetectable in undifferentiated hFM-MSCs (day 0), then it faintly appeared from day 7 to day 20, becoming abundant at days 29 and 42.…”
Section: Hfm-mscs Can Be Driven Toward a Da Neuronal Fatementioning
confidence: 99%